2002
DOI: 10.1038/sj.bjc.6600641
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of irinotecan with bolus and high dose infusional 5-FU and folinic acid (modified de Gramont) for first or second line treatment of advanced or metastatic colorectal cancer

Abstract: We investigated the activity of irinotecan given with a more convenient modified bimonthly de Gramont regimen of bolus and infusional 5-fluorouracil [IrMdG] in advanced or metastatic colorectal cancer in the first and second line setting. Irinotecan 180 mg m 72 was infused over 90 min. L-folinic acid 175 mg or d,l folinic acid 350 mg was given over 2 h followed by a bolus of 5-fluorouracil (400 mg m 72 ) and a 46 h continuous infusion of 5-fluorouracil (2.4 -2.8 g m 72 ). Forty-six previously untreated patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Several studies have shown that the modified de Gramont schedule is an active and well-tolerated regimen in combination with oxaliplatin or irinotecan [5,6,21,34]. Our study was a cost-minimization analysis considering effectiveness to be similar between the two regimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that the modified de Gramont schedule is an active and well-tolerated regimen in combination with oxaliplatin or irinotecan [5,6,21,34]. Our study was a cost-minimization analysis considering effectiveness to be similar between the two regimens.…”
Section: Discussionmentioning
confidence: 99%
“…We compared this a simplified de Gramont regimen that combines calcium folinate (400 mg/ m 2 as a 2-h infusion, day 1), 5-FU bolus (400 mg/m 2 , day 1), and 5-FU continuous infusion (2400 mg/m 2 as a 46-h infusion, day 1) [5,6,21,34]. In all cases the 5-FU continuous infusion was given using a portable disposable pump.…”
Section: Treatment Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…The MdG regimen is used to treat patients with incurable colorectal cancer and provides dose intensive exposure to 5‐Fluorouracil (5‐FU) every two weeks (Leonard et al. 2002).…”
Section: Infusion Regime In the Study Sitementioning
confidence: 99%
“…2002). The cytotoxic agent 5‐FU has been the mainstay of chemotherapy for colorectal cancer for more than 20 years (Leonard et al. 2002) and both the National Institute for Health and Clinical Evidence (2005) and the Scottish Intercollegiate Guidelines Network (2003) recommend ‘5‐FU containing’ regimens as first line treatment in colorectal cancer.…”
Section: Infusion Regime In the Study Sitementioning
confidence: 99%